Figures That Speak : The Vocabulary of Turkish Nationalism - deTar, Matthew (Book collections on Project MUSE., 2021)
"'Figures That Speak' builds a critical analysis of a vocabulary of 'figures' in Turkish public discourse that structure public thought and define the possibilities of political action: religion, the minority, the founding father (Atatürk), the military, and Europe. This unique focus on processes of representation and their circulation in public culture gives readers a new perspective on the effects of the way that contemporary politicians, journalists, academics, and the public all speak about international politics"--